Stiffness of flexible caisson foundations embedded in nonhomogeneous elastic soil - Doherty, J; Houlsby, G; Deeks, A (2005)
Solutions are presented for stiffness coefficients to represent the elastic behavior of a caisson foundation embedded in soil. The solutions use a novel numerical technique, the scaled boundary finite element method, combined with shell elements to represent the foundation itself. The stiffness coefficients take into account the possibility of nonhomogeneity in the soil (stiffness varying with depth), the geometry of the foundation, and the contribution to the stiffness of the skirt of the caisson foundation. Tabulated values allow a simple curve fit to the stiffness values to be employed for particular cases. The accuracy of the method is tested against previous solutions for particular cases. Example calculations are given to illustrate the method. Journal of Geotechnical and Geoenvironmental Engineering © ASCE.